1996
DOI: 10.1002/etc.5620151203
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the toxicity of metal‐spiked laboratory sediments using acid‐volatile sulfide and interstitial water normalizations

Abstract: Numerous studies have shown that dry weight concentrations of metals in sediments cannot be used to predict toxicity across sediments. However, several studies using sediments from both freshwater and saltwater have shown that interstitial water concentration or normalizations involving acid‐volatile sulfide (AVS) can be used to predict toxicity in sediments contaminated with cadmium, copper, nickel, lead, or zinc across a wide range of sediment types. Six separate experiments were conducted in which two or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
2
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 44 publications
10
184
2
8
Order By: Relevance
“…The AVS model that included the f OC in the normalization procedure also was highly predictive. Burton et al predicting metals toxicity also was shown in marine systems by Hansen et al [6] and supported by others [1,[2][3][4][7][8][9][10][11][12][13][14][15]. Organic carbon is a potentially important partitioning phase for metals in sediment and in water.…”
Section: Sem Avs and Ocmentioning
confidence: 73%
“…The AVS model that included the f OC in the normalization procedure also was highly predictive. Burton et al predicting metals toxicity also was shown in marine systems by Hansen et al [6] and supported by others [1,[2][3][4][7][8][9][10][11][12][13][14][15]. Organic carbon is a potentially important partitioning phase for metals in sediment and in water.…”
Section: Sem Avs and Ocmentioning
confidence: 73%
“…For several cationic metals, a number of studies have shown conclusively that, when acid‐volatile sulphide concentrations exceed those of metal simultaneously extracted, metal concentrations in the interstitial water are low and toxicity is not observed (e.g. Berry et al . 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of compelling field data, one of the best ways to gain insight into the toxicity and bioavailability of a metal in sediment is to perform spiked‐sediment toxicity tests [3]. Relatively few studies have been performed with freshwater sediments spiked with silver, and none have been performed with marine sediments.…”
Section: Introductionmentioning
confidence: 99%